Screening and identification of fungi having antimicrobial activity isolated from marine organisms and sediment samples taken in the Bai Tu Long, Vietnam - Duc Tuan, Cao; Thi Quyen, Vu; Mai Anh, Nguyen; Mai Huong, Doan Thi; Van Cuong, Pham; Anh Duy, Do; Young-Ho Kim; Hong Lien, Hoang Thi; Hong Minh, Le Thi (Vietnam Journal of Biotechnology, 2021)
Marine ecosystems cover about 70% of the planet surface and are still an underexploitedsource of useful metabolites. Among microbes, filamentous fungi are captivating organisms used for the production of many chemical classes of secondary metabolites used in various fields such as medicine, food ...The present study was focused on the collection, isolation and screening of fungi with antibacterial activity from 25 marine fungi strains isolated by concentration dilution method from 16 samples including marine organisms and sediments collected in Bai Tu Long, Vietnam. The strains were cultured in PDA medium and the culture broths were extracted by ethyl acetate and vacuum rotary evaporation to produce crude extracts. Antimicrobial activity of the extracts was carried out on 7 tested microorganisms, including three Gram-negative bacterial strains (Escherichia coli ATCC25922, Pseudomonas aeruginosa ATCC27853, Salmonella enterica ATCC13076), three Gram-positive strains (Enterococcus faecalis ATCC29212, Stapphylococus aureus ATCC25923, Bacillus cereus ATCC14579), and yeast Candida albicans ATCC10231. The screening results showed thatfour strains with the highest antibacterial activity (M403, M583, M584 and M612) were capable of inhibiting 4 of the 7 tested microorganisms with minimum inhibitory concentration (MIC) from 32 to 256 µg/mL depending on each tested strain. Specifically, all M403, M583, M584 and M612 inhibited C. albicans ATCC10231 with MIC values ​​of 32-32-64-128 µg/mL, respectively. In addition, all four strains showed inhibitory activity against all three Gram-positive strains tested with MICs from 64 to 256 µg/mL. The strains were identified by morphology and 18S rRNA gene sequences. The results showed that 18S rRNA gene sequences of strains hadover 99% similarity with the 18S rRNA gene sequences available on the Genebank database. Strain M403 was most closely related Aspergillus versicolor and M584 was most closely related Aspergillus unguis, whereas M583 was most closely related Talaromyces purpureogenus and M612 identified as a member Penicillium chrysogenum. The sequences of 18S rRNA gene of four strains were registered on GenBank database with accession numbers: M403 (MW479130), M583 (MW479131), M584 (MW015805) và M612 (MW015801). Preliminary results showed that the marine environment has great potential for isolating fungal strains which contain antibacterial and other bioactive substances.